In Search for Excellence in Global Production Networks - Ocicka, Barbara (W poszukiwaniu doskonałości w globalnych sieciach produkcji, 2010)
The article indicates a possibility of the transition of the role of foreign factories from the offshore low cost production sites to the lead centres of process excellence. Firstly, the author outlines changes in geographical scope and configuration of global production networks, underlining the importance of so called low cost countries located in South and Eastern Asia, Central and Eastern Europe as well as in Central and South America. Secondly, the evolution of the role of foreign factories is carefully explained in the light of methodology proposed by K. Ferdows. Additionally, best practice case of BSH Sprzęt Gospodarstwa Domowego Sp. z o.o. is presented to illustrate its process excellence in global production network.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 126, s. 369-378
Keywords: global production networks; process excellence; low cost countries